2020
DOI: 10.1186/s12889-020-8176-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression in rural Pakistan: the protective associations with cultural postpartum practices

Abstract: Background: Traditional postpartum practices are intended to provide care to mothers, but there is mixed evidence concerning their impact on postpartum depression (PPD). It remains unknown if there is a unique impact of postpartum practices on PPD separately from other types of social support, or if practices differentially affect those with existing prenatal depression. In Pakistan, chilla (‫چ‬ ‫ل‬ ‫ه‬) is a traditional postpartum practice in which women receive relief from household work, additional familial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In this study, postpartum depressive symptoms were found among one-third of mothers which accounted for 33.7% (95% CI: 29.2–38.5%). This finding is consistent with previous studies undertaken in a different time in different areas, where the prevalence of PPD among mothers during this course were 30.3% in Paropakar Maternity and Women’s Hospital (PMWH), Kathmandu, Nepal [ 21 ], 34.6% in South-East Nigeria [ 21 ], about 39.4% in urban slums of Dhaka, Bangladesh [ 16 ] and 34.6% in Karachi, Pakistan [ 41 ] using EPDS score. In Nepal, Several studies reported the prevalence of postpartum depressive symptoms among mothers were ranging from 10–30% during different periods in the different settings using an EPDS score cut-off ≥10–13 [ 20 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, postpartum depressive symptoms were found among one-third of mothers which accounted for 33.7% (95% CI: 29.2–38.5%). This finding is consistent with previous studies undertaken in a different time in different areas, where the prevalence of PPD among mothers during this course were 30.3% in Paropakar Maternity and Women’s Hospital (PMWH), Kathmandu, Nepal [ 21 ], 34.6% in South-East Nigeria [ 21 ], about 39.4% in urban slums of Dhaka, Bangladesh [ 16 ] and 34.6% in Karachi, Pakistan [ 41 ] using EPDS score. In Nepal, Several studies reported the prevalence of postpartum depressive symptoms among mothers were ranging from 10–30% during different periods in the different settings using an EPDS score cut-off ≥10–13 [ 20 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…This transitioning phase is called chilla in the regional language and lasts for 6 weeks after the birth of the baby. Perhaps this transition of a socially active pregnant woman to a narrow social role of a postpartum woman may explain why the family, spouses, and friends are no longer seen as three distinct sources of social support in the postpartum period (Lemasters et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was later crossculturally adapted for use among postpartum women in Pakistan, by Akhtar et al (2010). However, Akhtar et al (2010) found it to have a unidimensional construct in Pakistan, perhaps due to its relevance to postpartum women and the traditional birthing practice of chilla in the postpartum period (Lemasters et al, 2020). In addition, this disparity in factor structure may have resulted due to traditional statistical heuristics utilized by Akhtar et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Pakistan over the past decade have set the prevalence range between 22% and a whopping 60% for anxiety and depression (Ahmed, Enam, Iqbal, Murtaza, & Bashir, 2016). These high rates coupled with an annual population growth rate of 2.4% (Pakistan Bureau Of Statistics, 2017) warrants a look at the mental health of the caretakers of the future generation(Niloufer Sultan Ali, Mahmud, Khan, & Ali, 2013;Gulamani, Shaikh, & Chagani, 2013;LeMasters et al, 2020;Maselko et al, 2016;Rahman, Lovel, Bunn, Iqbal, & Harrington, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of maternal health and well-being is as important for the growth and development of young children as it is for the mother (Nusrat Husain et al, 2017;Naerde, Tambs, Mathiesen, Dalgard, & Samuelsen, 2000). This consideration of adverse effects on the children calls for urgent focus to maternal mental health beyond that of the pregnancy and post-partum period that has been studied relatively more in our population (Niloufer S Ali, Azam, Ali, Tabbusum, & Moin, 2012;Niloufer Sultan Ali et al, 2013;Gul, Sherin, Jabeen, & Khan, 2017;Gulamani et al, 2013;LeMasters et al, 2020;Rahman et al, 2004;Shah & Lonergan, 2017).…”
Section: Introductionmentioning
confidence: 99%